Psychometric evaluation of the Kaufman Assessment Battery for Children, Second Edition (KABC-II) in rural South Africa - Mitchell, Joanie Marie (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015